Superelastic stress–strain behavior in ferrogels with different types of magneto-elastic coupling. Issue 38 (16th September 2016) - Cremer, Peet; Löwen, Hartmut; Menzel, Andreas M.
Abstract : Anisotropic ferrogels and magnetorheological elastomers allow for reversible tunability of their markedly nonlinear stress–strain properties. Abstract : Colloidal magnetic particles embedded in an elastic polymer matrix constitute a smart material called a ferrogel. It responds to an applied external magnetic field by changes in elastic properties, which can be exploited for various applications such as dampers, vibration absorbers, or actuators. Under appropriate conditions, the stress–strain behavior of a ferrogel can display a fascinating feature: superelasticity, the capability to reversibly deform by a huge amount while barely altering the applied load. In previous work, using numerical simulations, we investigated this behavior assuming that the magnetic moments carried by the embedded particles can freely reorient to minimize their magnetic interaction energy. Here, we extend the analysis to ferrogels where restoring torques by the surrounding matrix hinder rotations towards a magnetically favored configuration. For example, the particles can be chemically cross-linked into the polymer matrix and the magnetic moments can be fixed to the particle axes. We demonstrate that these systems still feature a superelastic regime. As before, the nonlinear stress–strain behavior can be reversibly tailored during operation by external magnetic fields. Yet, the different coupling of the magnetic moments causes different types of response to external stimuli. For instance, an external magnetic field applied parallel to the stretching axis hardly affects the superelastic regime but stiffens the system beyond it. Other smart materials featuring superelasticity, e.g. metallic shape-memory alloys, have already found widespread applications. Our soft polymer systems offer many additional advantages such as a typically higher deformability and enhanced biocompatibility combined with high tunability.